POLA ASUH ORANGTUA DENGAN KEJADIAN STUNTING PADA BALITA DI KELOMPOK BKB HI - Kumala Sari Rambe (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Stunting or the condition of growth failure in children due to malnutrition is caused by various aspects, ranging from inadequate maternal knowledge, repeated infections, poor sanitation, limited health services or even a combination of all aspects. Therefore, the identification of the main causes of stunting is very important to facilitate efforts to solve it. The type of research used was observational analytic with a cross sectional design. The population in this study were mothers who had toddlers (1-5 years) as many as 40 mothers. The sample in this study using the Acidental Sampling technique. The results of the bivariate analysis test using a simple Chi-square test showed that there was a significant relationship between eating parenting and the incidence of stunting (p < 0.038). there is a significant relationship between health care patterns and the incidence of stunting (p < 0.027). There is no significant relationship between psychosocial parenting and the incidence of stunting (p < 0.205). Suggestions for parents, especially mothers, are expected to pay more attention to food diversity by increasing daily food variations and providing quality time to support activities and accept child behavior that has not been controlled patiently and without coercion or punishment for children.